The Prospect of Indonesian Herbal as An Alternative Treatment for Covid-19 Patient: A Literature-Based Study - SUNARYO, HADI; Hidayati, Wahyu (UI Scholars Hub, 2024)
Coronavirus disease 2019 (COVID-19) is a new disease caused by a novel coronavirus, Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). The disease has several symptoms from mild to severe and could lead to death for comorbidities and the elderly. Therefore, the infections and mortality cases keep growing day by day, moreover many authorities are trying to suppress it by applying several health protocols, including medicines. Several studies were conducted on drug discovery from plants to cure the disease. The article aimed to do a narrative review about the prospect of JAMU becoming an alternative medicine to cure COVID-19 by mapping the literature deposited on PubMed which reported medicinal plants as an alternative medicine for COVID-19 by using a text mining program. There are approximately 30,191 articles on PUBMED related to COVID-19 and medicine. Medicinal plants with antiviral and anti-inflammatory activities are the best plants for COVID-19. JAMU, an Indonesian traditional medicine, has an outstanding possibility to be applied in the COVID-19 strategy to recover patients and prevent infections.